Real-life drug retention rate and safety of rituximab when treating rheumatic diseases: a single-centre Swiss retrospective cohort study - Alexandre Dumusc; Fahad Alromaih; Matthieu Perreau; Thomas Hügle; Pascal Zufferey; Diana Dan (Arthritis Research & Therapy, 2023)
Abstract Background In Switzerland, rituximab (RTX) is licenced for the treatment of rheumatoid arthritis (RA) and ANCA-associated vasculitis (AAV) but is frequently used off-label to treat other auto-immune diseases (AID), especially connective tissue diseases (CTD). We aimed to characterise the use of RTX in AID in a real-life Swiss setting and compare RTX retention rates and safety outcomes between patients treated for RA, CTD and AAV. Methods A retrospective cohort study of patients who started RTX in the Rheumatology Department for RA or AID. The RTX retention rate was analysed using Kaplan–Meier survival curves. Occurrences of serious adverse events (SAE), low IgG levels and anti-drug antibodies (ADA) were reported. Results Two hundred three patients were treated with RTX: 51.7% had RA, 29.6% CTD, 9.9% vasculitis and 8.9% other AIDs. The total observation time was 665 patient-years. RTX retention probability at 2 years (95%CI) was similar for RA and CTD 0.65 (0.55 to 0.73), 0.60 (0.47 to 0.72) and lower for vasculitis 0.25 (0.09 to 0.45). Survival curves for RTX retention matched closely (p = 0.97) between RA and CTD patients but were lower for patients with vasculitis due to a higher percentage of induced remission. Patients with vasculitis (95%) and CTD (75%) had a higher rate of concomitant glucocorticoid use than RA (60%). Moderate to severe hypogammaglobulinaemia was observed more frequently in patients with vasculitis (35%) than with RA (13%) or CTD (9%) and was associated with an increased risk of presenting a first infectious SAE (HR 2.01, 95% CI 1.04 to 3.91). The incidence rate of SAE was 23.3 SAE/100 patient-years (36% were infectious). When searched, ADAs were observed in 18% of the patients and were detected in 63% of infusions-related SAE. 10 patients died during RTX treatment and up to 12 months after the last RTX infusion, 50% from infection. Conclusion RTX retention rates are similar for patients with RA and CTD but lower for those with vasculitis due to more frequent remission. Patients treated with RTX for vasculitis present more SAE and infectious SAE than patients with RA and CTD, potentially due to a higher use of concomitant glucocorticoids and the occurrence of hypogammaglobulinaemia.